Improving the Character of Tolerance Between Friends through Contextual Learning in Islamic Education Learning at SD Negeri No. 105406 Pematang Guntung - Hilaliyah; Kodar, Arbainur (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This research aims to increase tolerance between friends through the application of contextual learning on moral material towards others in grade V of SD Negeri No. 105406 Pematang Guntung. The background of this study is the low tolerance of students in daily life in the school environment, which is shown by the lack of ability to accept differences, the emergence of small conflicts between students, and lack of mutual respect. Contextual learning was chosen as an approach because it is able to relate the subject matter to the real situation faced by students, so it is expected to be easier to understand and apply in social life. The research method used is Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation of actions, observation, and reflection. Data collection techniques are carried out through direct observation of student behavior, interviews with teachers and students, and documentation of learning activities. The results of the study showed that students' tolerance attitudes experienced a significant increase after the implementation of contextual learning. The improvement can be seen in the ability of students to work together in groups, respect each other's opinions, and show empathy for existing differences. Thus, the application of contextual learning in moral material to others has proven to be effective in fostering tolerance among elementary school students. These results recommend using a similar approach to form other positive characters in students.